A Cross-Sectional Study of the Distribution Patterns and Potential Determinants in Plasma Selenium Status Among Chinese Adults With Hypertension - Wang, Zhuo; Lin, Tengfei; Wei, Yaping; Song, Yun; Liu, Lishun; Zhou, Ziyi; Huang, Xiao; Chen, Ping; Liu, Chengzhang; Li, Youbao; Wang, Binyan; Li, Jianping; et al. (Frontiers in Nutrition, 2022)
Selenium (Se) is an essential trace element in selenoproteins biosynthesis for the human body and plays an important role in the prevention and control of subsequent cardiovascular disease in adults with hypertension. However, reports on Se status and its potential determinants in populations from different regions of China are limited, especially data on adults with hypertension, a high-risk group more vulnerable to oxidative stress. Thus, we conducted a cross-sectional study from February 2017 to May 2018 of 2,599 participants (1,389 men and 1,210 women) on middle-aged to elderly adults with hypertension with a mean age of 63.1 years (SD 13.3) from 14 provinces of China and aimed to examine the relationship of plasma Se status with demographic characteristics and lifestyles. Overall, the male participants (mean value 75.0 μg/L) tended to have higher plasma Se concentrations than the female participants (73.7 μg/L) when controlling for relevant factors. There were significant differences among regions, and in age and body mass index (BMI) in plasma Se distribution, and plasma Se concentrations were significantly lower among those in the regions with relatively lower Se, aged 60 years or older, and with BMI lower than 28 kg/m2. Moreover, a higher frequency of meat consumption (1–2 or ≥3 times/week vs. <1 time/week) was significantly associated with higher plasma Se concentrations in men and women, and male alcohol drinkers had significantly higher plasma Se concentrations than non-alcohol drinkers. Adequate consumption of fruits and vegetables (0.5–1.5 kg/week) was associated with higher plasma Se concentrations among women, but was associated with relatively lower plasma Se concentrations in men. Our results indicated relatively low plasma Se status in Chinese adults with hypertension from 14 provinces, while specific factors including geographic, demographic, and lifestyle characteristics and blood pressure were significantly associated with plasma Se status in this hypertensive population. In addition, more studies are required to further evaluate dietary structure and other lifestyle factors that influence circulating Se status.